Social Mapping of Clean and Healthy Life Behavior of Remote Indigenous Communities in Kampung Ulakin Kolf Brasa District Asmat Regency Papua Province - Urip Wahyudin (Asian Social Work Journal, 2019)
This social mapping aims to collect data and information about clean and healthy life behavior (PHBS) of Remote Indigenous Communities (KAT) in Ulakin Village, Kolf Brasa District, Asmat Regency, Papua Province. The method of data collection in this study is survey method. Data collection techniques used; 1) observation, 2) interviews with leaders and community members, and 3) focus group discussions. The results of the study show that; 1) childbirth assistance has not been carried out by health workers, 2) babies have been breastfed, 3) the community does not have health insurance, 4) the community still utilizes the availability of rainwater and rivers, 5) some houses have used healthy toilets as facilities from the local government, but not yet utilized as appropriate, 6) the average floor area of a house is 36 m2 with an average occupant of 3-5 people, 7) the floor of the house is made of wooden boards which are assistance from the government, 8) the community still smokes in any place, including inside the house, 9) the community always engages in physical activities in the context of hunting and gathering activities, 10) the community eats fruit and vegetables irregularly, adapted to natural resources and the environment. Suggestions for this research; 1) the parties involved have to carry out a more comprehensive follow-up study, and 2) the community as beneficiaries should receive information, services, guidance and social assistance in a participatory, measurable and sustainable manner.